2002
DOI: 10.1007/s00425-001-0732-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of actin gene isoforms in the Arabidopsis leaf measured in microsamples from intact individual cells

Abstract: The contents of single plant cells can be sampled using glass microcapillaries. By combining such single-cell sampling with reverse transcription-polymerase chain reaction (RT-PCR), transcripts of individual genes can be identified and, in principle, quantified. This provides a valuable technique for the analysis and quantification of the intercellular distribution of gene expression in complex tissues. In a proof-of-principle study, the cellular locations of the transcripts of the eight isoforms of actin (ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…When sampling material for cell microdissection, the possibility of contamination of the sample (Nakazono et al 2003) can never be entirely eliminated, whatever sampling technique is used (Laval et al 2002). Based on careful observations of their histological sections, Ornstein et al (2000) estimated each dissection by laser cell microdissection to contain more than 95% of the desired cells, which is similar to our findings with lyophilized cryosection microdissection.…”
Section: Producing Cell-type Enriched Samplessupporting
confidence: 78%
“…When sampling material for cell microdissection, the possibility of contamination of the sample (Nakazono et al 2003) can never be entirely eliminated, whatever sampling technique is used (Laval et al 2002). Based on careful observations of their histological sections, Ornstein et al (2000) estimated each dissection by laser cell microdissection to contain more than 95% of the desired cells, which is similar to our findings with lyophilized cryosection microdissection.…”
Section: Producing Cell-type Enriched Samplessupporting
confidence: 78%
“…MUBI1-5 (5Јggtggtatgcagatctttg3Ј) and MUBI1-6 (5Јgtagtctgctagggtgcg3Ј) for 182 bp product BS-specific ME primers MEFOR (5Јcaggttgttagcagcactcaag3Ј) and PMEL (5Јcaatgcctctccagcag-cacc3Ј) for 965 bp product; 1350C (5Јcgctccaattgaagagtgcgcaag3Ј) and RTP-MEL (5Јcagggactataaacaacagagtac3Ј) for 791 bp product; ML1415 (5Јggctc-ccttcagccattcaag3Ј) and 1927L (5Јcggtagacgggagtgtacatg3Ј) for 613 bp product Actin8 primers (Laval et al, 2002) AACT8F (5Јctaactaaagagacatcgtttcca3Ј) and AACT8R (5Јgtttttatccgagttt-gaagaggct3Ј) for 250 bp product Carbonic anhydrase primers CACPF (5Јgacttcatagaggactgggtc3Ј) and CACPR (5Јaatgtagtatggtagcca-catc3Ј) for 292 bp product.…”
Section: Ubiquitin Primersmentioning
confidence: 99%
“…For ACT2, primers CTAAGCTCTCAAGATCAAAGGCTTA and ACTAAAACGCAAAACGAAAGCGGTT were used to amplify 218 bp of the cDNA sequence. ACT2 was chosen as an internal reference because we have previously shown that it is expressed in a wide variety of cell types in Arabidopsis (Laval et al, 2002) and, from microarray data, that expression of ACT2 appears to be broadly constitutive: In particular, levels of ACT2 transcripts are unaffected by CaMV infection (V. Laval, J. Laird, P. Armengaud, and J.J. Milner, unpublished data). To avoid amplification of cDNAs encoded by gene homologs, primers were designed to generate an amplicon from the 3# noncoding region of both transcripts.…”
Section: Assay Of Mrna By Quantitative Hybridizationmentioning
confidence: 99%
“…To avoid amplification of cDNAs encoded by gene homologs, primers were designed to generate an amplicon from the 3# noncoding region of both transcripts. Regression lines were generated using, as external standards, DNA from plasmids containing fulllength cDNA sequences of ACT2 and GST1 Laval et al, 2002). For each sample, values for the concentration of GST1 cDNA were calculated by normalizing the raw values for GST1 using the concentration of ACT2 as an internal reference.…”
Section: Assay Of Mrna By Quantitative Hybridizationmentioning
confidence: 99%